"It Is Divine Punishment for Our Sins" Knowledge and Perception of the Cause, Symptoms, and Mode of Transmission of the COVID-19 Disease Among Local Traders in Nigeria - Olubukola Omobowale; Adeola Fowotade; Temiloluwa Iyanda (Gonabad University of Medical Sciences, 2022)
Background: Access to correct information can influence the formation of the right attitude towards mitigating the spread of the COVID-19. Many individuals in Nigeria have taken up non-scientifically approved practices in a bid to protect themselves from the virus. The aim of this study was to assess the source of information, and knowledge of the cause and mode of transmission of the COIVD-19 among local traders in Ibadan, Oyo State, Nigeria. Methods: A cross-sectional study of local traders from two densely populated markets in Ibadan was conducted using an interviewer-administered semi-structured questionnaire. Data were analyzed using SPSS software v. 25 and Microsoft Excel 2016 and were presented in frequency tables and charts. The Chi-square test was used to test the associations. The level of significance was set at P<0.05. Results: A total of 321 traders (27.4% were males and 72.6% were females) were recruited with a Mean±SD age of 39.4±11.8 years. Radio (93.5%) and television (75.7%) were the most commonly used sources of information, 65.8% believed that COVID-19 was a result of divine punishment for sins and the majority (95.3%) reported that COVID-19 was spread through personal contact with infected persons. There was a statistically significant association between knowledge of cause and age (P=0.004), as well as between knowledge of cause and marital status (P=0.001). Additionally, a statistically significant association was observed between knowledge of transmission and level of education (P=0.012). Conclusion: Even though they have access to adequate information, people may not take proper actions to protect themselves and others from contracting the COVID-19. Reinforced health promotion strategies that pay attention to the local contexts and perspectives of community members should be taken across the board.